Implementasi Instrumen Portofolio dalam Mengukur Kemampuan Berpikir Kritis Siswa Kelas X IPS 1 MAN 1 Bantul pada Mata Pelajaran Sejarah - Dito Fernando; Adnan Hidayat Purnama; Luqdina Aprilia Hapsari; Lusia B. Rebon (Jurnal Ilmiah Kanderang Tingang, 2023)
The problem found in this study is the difficulty of students in thinking critically. This study aims to determine the ability to think critically in the process of discussing history in class X IPS 1 at MAN 1 Bantul, the efforts of teachers to improve critical thinking skills in discussions, and the obstacles faced by teachers and students in increasing critical thinking in discussions. 1) Based on the results of data obtained from 30 students of class X IPS 1 students' critical thinking skills have the highest score on the persistence indicator of 70.67% in the medium category, the solution indicator is 69.33% in the medium category, logical reasoning indicators, evaluation arguments, and decision making by 68.67% in the medium category, collaboration indicators by 68% in the medium category, information analysis indicators by 67.33% in the medium category, problem identification indicators and argument indicators by 66.67% in the medium category, creativity indicator of 61.33% with low category. 2) the teacher's effort to improve students' critical thinking in history learning is to use the presentation method followed by discussion. 3) Obstacles faced by students of class X IPS 1 MAN 1 Bantul, namely difficulties in studying and analyzing a history learning topic during discussion activities.